Characterisation of Australian Staphylococcus aureus isolates of bovine mastitis origin, and development and evaluation of the potential of vaccines for prevention of mastitis using mouse as a model system - Gogoi Tiwari, Jully (Curtin University, 2014)
Serological typing was demonstrated to be more reliable than molecular typing for capsular phenotyping of Australian bovine mastitis-associated Staphylococcus aureus isolates. A relationship between strength of biofilm formation, icaA and icaD genes and extent of mammary tissue damage was apparent. Distribution of MSCRAMMs and exotoxins, and potential of anti-IL6 and anti IL6-receptor antibodies on mortality of infected mice was determined. Biofilm-embedded S. aureus vaccine offered better protection against mammary tissue damage than the planktonic vaccine.